Observations of the scoliid wasp Campsomeriella annulata annulata (Fabricius, 1793) foraging on fallen Firmiana simplex flowers - Yamazaki, Kazuo (Entomological Communications, 2024)
A scoliid wasp, Campsomeriella annulata annulata (Fabricius, 1793) (Hymenoptera: Scoliidae), was observed foraging on Firmiana simplex flowers that had fallen onto shrubs in an urban park in central Japan. The wasp inserted its glossa into the tubular corolla of each fallen flower, foraging from eight different fallen male flowers within five minutes before flying away. This finding suggests that scoliid wasps may engage in atypical flower visitation, or that foraging from fallen flowers could reduce interspecific competition for floral resources.